Digitalization of Teaching Materials in Literature Learning As Reinforcement of Human Values - Zuliyanti Zuliyanti; Agus Nuryatin; Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2022)
The purpose of this study is to explain the role of digitizing teaching materials in literature learning as a reinforcement of humanist values. This research method is descriptive analysis with research steps: identifying, classifying, analyzing, and concluding data. The research data is in the form of information on the process of learning literature in schools and the use of digitalization as a multi-interactive media to strengthen humanist values. Data collection instruments & techniques: observation sheets, interview guides, and data cards. Analysis of the data used qualitative analysis which includes identification, reduction, analysis, and generalization. The result of this study is that literary learning is very urgent to be optimized by using digitalization, including digital teaching materials. The digitization of literary learning teaching materials can be optimized from the use of digital learning resources as a support for literary learning. The presentation of digital teaching materials in literary learning can be considered in terms of material, language, presentation, and graphic aspects. Literature learning has the opportunity to teach moral values, including humanist values. Some humanist values ​​that can be optimized in literary learning include (1) peace, (2) respect, (3) responsibility, (4) happiness, (5) freedom, (6) tolerance, (7) cooperation, (8) love, (9) simplicity, (10) unity, and (11) humility.